Occurrence of P392L mutation in ethnic Thai with Chinese descent paget’s disease - Vorachai Sirikulchayanonta (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: The etiology of Paget’s disease is still unclear. However, the available evidence shows that genetics plays an important role in its pathogenesis. Although the disease is genetically heterogeneous, mutations of SQSTM1 gene, especially missense mutation P392L, are reportedly the most common genetic polymorphism associated with it. To the best of our knowledge, data regarding mutations of this gene have mainly been obtained from patients of European descent. The authors hypothesized that the P392L mutation might also play a role in Paget’s disease among Asian ethnic groups. Unfortunately, due to the rarity of the cases, data regarding mutations among Asian ethnic groups, especially those from Southeast Asian countries are sparse in the literature. Objective: To find the occurrence of P392L mutation in Paget’s disease among ethnic Thai group. Materials and Methods: A genetic analysis was carried out using archived material from four ethnic Thai patients with Paget’s disease. DNA was extracted from formalin-fixed, paraffin embedded tissue for specific PCR targeting of 326 bp of the SQSTM1 gene (exon 8). Amplicons were sequenced bidirectionally using an ABI PRISM 3730XL (Applied Biosystems, USA) sequencer using T7 promoter and SP6 primers. Results: No P393L mutations in the SQSTM1 protein (exon 8) were found in any of these four cases. Conclusion: These results were similar to those obtained from previous studies on patients of Chinese descent. A combined analysis of the present data and that from 21 previously-reported, sporadic cases of Paget’s disease in Asian patients revealed absence of the P392L mutation but presence of one different mutation (1/25 = 4%).